Pedagogical models and their relationship with the conceptions of law: meeting points with education in law - Garzón-Saladen, Álvaro; Romero-González, Zilath (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The study of the pedagogical models have important connection to the views of law because they must be in line with the object of the educational process in law studies and the theories of both the law and its law culture. This paper is part of the theorethical surveys whose approach is hermeneutic, dialogic law and pedagogic has a whole view of the process of teaching and learning in law studies. The insights show that the contributions made by the law pedagogic admit the existence of game of arguments as strategies to learn and re-learn the law context phenomena making posible a new awareness of what is law. To close it can be said that the pedagoic view influences the formation of the lawyer therefore the pedagogic model needs to offer the usage and the compenetration of the law citizen auscultation as profesional person in this field with an influecing power in the social reality.